Interaction quality and satisfaction: An empirical study of international tourists when buying Shanghai tourist attraction services - Lilian Consuelo Mustelier-Puig; Amna Anjum; Xu Ming (Cogent Business & Management, 2018)
The main purpose of this article is to examine the relationship between the quality of interaction with tourist attraction services and satisfaction. The model proposes that interaction quality (IQ) affects both satisfaction with tourism services and the overall tourist satisfaction (OTS) with the destination. In addition, the link between the OTS and the intention to revisit the destination is assessed. Data were collected from 165 international tourists visiting Shanghai tourist attractions and analyzed through PLS-SEM using second-order hierarchical modeling. IQ is seen as a multidimensional construct, including aspects such as language, nonverbal behavior, attitude, and expertise. The results confirm the direct effect of IQ on service satisfaction and the OTS as well as its indirect effect on revisit intention. The overall tourist's satisfaction does directly impact the intention to revisit the destination. For international tourists visiting Shanghai, IQ constitutes an essential part of their experience not only with services rendered but also with the destination itself.
Keywords: 650